Effect of temperature and fermentation time on protease production using decapterus macarellus fish waste - Noralia Mohd Alias,; Chua, Chua, Gek Kee; Chew, Few Ne; Noraziah Abu Yazid,; Rozaimi Abu Samah,; Siti Hatijah Mortan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The fish processing industries generate huge amounts of by-products which cause serious environmental and health problems. The environmental problems related to waste disposal can be reduced as the low cost of fish by-products contains nutrients that can enhance microbial growth and are useful for enzyme production. This research aims to investigate the effect of temperature and fermentation time on protease production from fish waste hydrolysate by using the Bacillus strain (Bacillus cereus). The pre-treatment and fish waste hydrolysate were carried out and continued with the production of protease. The effect of fermentation time was studied every 4 h for 72 h while the effect of temperature was investigated at temperatures ranging from 30 °C to 60 °C. The results showed the maximum protease production of 45.63 U/mL at 48 h of fermentation time and 44.908 ± 6.14 U/mL at a temperature of 50 °C. The current study provides insight into the effects of cultivation conditions on protease production from local fish waste industries for further optimization study to enhance protease production.